Analysis of Causality Relationship Between the Economic Growth and the Energy Production and Technological Investments in Kazakhstan - Myrzabekkyzy, Kundyz; Keneshbayev, Bektur; Razakova, Dina I.; Kenzhebekova, Indira; Pirmanova, Zhansulu (International Journal of Energy Economics and Policy, 2022)
This study analyzes the causality relationship between economic growth and energy production (Electricity and Thermal Energy) and technological investments in Kazakhstan between 1993 and 2020 using Cointegration and Vector Error Correction Models (VECM), and also performs impact analysis. Cointegration analysis was used to determine whether there is a long-term relationship between the variables that became stationary after the first difference. Energy production proved to be an important contributor to the economic growth of Kazakhstan. Compared to energy production, technology investments have a more decisive effect on economic growth. Therefore, the importance of technology investments for countries has been emphasized once again.